Organic-based material as an alternative for packaging food products (Research, Society and Development, 2022)
Contemporary society is increasingly being marked by discourses about the environment, sustainability and the need for sustainable and ecologically correct consumption. For this speech, organic food has been gaining more prominence in the Brazilian and world scenario. With the growing demand for these products, questions about packaging arise. Knowing that the world consumption of plastic has been increasing, causing serious environmental problems due to its inability to biodegrade; the use of renewable resources has been explored, which can reduce waste disposal problems. Consequently, the development of organic-based biodegradable materials emerge as an alternative to this packaging. Therefore, this study aims to present a narrative bibliographic survey addressing the topic related to organic food and biodegradable and organic packaging. For the narrative review, searches were carried out in databases such as: SCIELO, Science Direct, PubMed and national and international websites related to the topic. Based on the study, among the alternatives for producing an organic-based film, starch is one of the most researched bases and considered a good substitute for traditional packaging. However, there is a need to add a plasticizer in its formulation, so the incorporation of a natural plasticizer, which may be organic, should be investigated by future research. This organic-based material can be used in different food products.